2020
DOI: 10.1042/bsr20194143
|View full text |Cite|
|
Sign up to set email alerts
|

RASA1 inhibits the progression of renal cell carcinoma by decreasing the expression of miR-223-3p and promoting the expression of FBXW7

Abstract: Abstract RAS p21 protein activator 1 (RASA1), also known as p120-RasGAP, is a RasGAP protein that functions as a signaling scaffold protein, regulating pivotal signal cascades. However, its biological mechanism in renal cell carcinoma (RCC) remains unknown. In the present study, RASA1, F-box/WD repeat-containing protein 7 (FBXW7), and miR-223-3p expression were assessed via quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and Western blot. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…The results revealed miR-223-3p could bind directly to solute carrier family 4, member 4 (SLC4A4) mRNA, and reduced SLC4A4 mRNA and protein expression, which was associated with KRAS signaling and epithelial-mesenchymal transition [ 36 ]. Besides, Zhang et al's study confirmed the carcinogenesis of miR-223-3p and found RASA1 may play a key role in the progression of RCC by decreasing miR-223-3p and subsequently increasing FBXW7 expression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed miR-223-3p could bind directly to solute carrier family 4, member 4 (SLC4A4) mRNA, and reduced SLC4A4 mRNA and protein expression, which was associated with KRAS signaling and epithelial-mesenchymal transition [ 36 ]. Besides, Zhang et al's study confirmed the carcinogenesis of miR-223-3p and found RASA1 may play a key role in the progression of RCC by decreasing miR-223-3p and subsequently increasing FBXW7 expression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…RASA1 inhibits renal tissue brosis by reducing myo broblasts proliferation 19 . In kidney carcinoma, RASA1 reduces miR-223-3p expression to inhibit the proliferation and differentiation of renal cell carcinoma 20 . YT521-B homology domain containing 2(YTHDC2) is an m6A reader that expedites messenger ribonucleic acid (mRNA) decay.…”
Section: Discussionmentioning
confidence: 99%
“…PFKL-WT or PFKL-MUT was co-transfected with miR-185-3p mimic into H1299/ER or A549/ER cells. After transfection for 48 h, H1299/ER and A549/ER cells were evaluated using the Reporter Vector System (AM5795, Invitrogen, CA, United States) using a GloMax 20/20 Luminometer (Promega, WI, United States) ( Zhang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%